Study on the Current Situation and Development Countermeasures of Basketball Clubs in Colleges and Universities of Dongguan City - Tian, Jian (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
The establishment of clubs provides a platform for college students to exert their subjective initiative. With the proposal of China’s lifelong sports and national fitness policies, the degree of sports socialization has been continuously improved. The number of college students participating in sports activities is increasing, and sports clubs are emerging one after another. College basketball clubs are a new product emerging from school reforms in the new era. The development of these clubs can meet the needs of students’ personalized development, strengthen their specialties, cultivate their interests, and thus have a promising development prospect. This paper conducts an in-depth study on the current situation and existing problems of basketball clubs in colleges and universities of Dongguan City by means of literature review, questionnaire survey, and interviews. It puts forward improvement strategies for the problems existing in the development of basketball clubs, which is of certain guiding significance for the dissemination and healthy development of basketball clubs in colleges and universities of Dongguan City. This study mainly conducts specific investigations and researches on the member status, material resources, system construction, and activity organization of basketball clubs in colleges and universities of Dongguan City. The results are, first the construction of basketball clubs in colleges and universities of Dongguan City has been improved. It also showed that the material foundation of basketball clubs in colleges and universities of Dongguan City is insufficient and the system construction of basketball clubs in colleges and universities of Dongguan City needs to be improved. Last, the organized activities of basketball clubs in colleges and universities of Dongguan City are single. In order to further develop and expand the clubs, inter-college exchanges should be strengthened.